PENGARUH EARNING PER SHARE (EPS), DEBT TO EQUITY RATIO (DER) DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2007-2011) - Arum Desmawati Murni Mussalamah; Muzakar Isa (Benefit Jurnal Manajemen dan Bisnis, 2016)
The aim of this study is to test the effect of Earning Per Share (EPS), Debt to Equity Ratio (DER), and Return On Equity (ROE) to stock price. This study was chosen because there were still differences between one study and another. There was also distinct condition between theory and the reality.